Dinamika Resiliensi Wanita pada Masa Emerging Adulthood yang Kehilangan Ayah Karena Serangan Jantung - Tantoro, Patricia Irewa; Wandansari, Yettie; Tedjawidjaja, Detricia (Universitas Trunojoyo Madura, 2025)
The sudden death of a loved one is a painful experience, especially for young women who face their own challenges, such as financial issues and marriage. The abrupt loss of a father can lead to complex grief. In such situations, resilience is crucial for individuals to endure and rise from adversity. Resilience is the ability to adjust, adapt, endure, and recover from hardships. This research aims to explore the dynamics of resilience in women during emerging adulthood who lost their fathers to a heart attack, using a qualitative research method and a phenomenological approach. The findings indicate three phases the participants faced in achieving resilient personalities: the initial, adjustment, and resurgence phases. The initial stage encompasses disbelief reactions, while the adjustment phase entails endeavors to return to previous circumstances. The resurgence phase is marked by the ability to rebound, find positivity, spiritual insights, psychological growth, a desire for personal improvement, positive outlooks, and managing persisting challenges. Factors that contribute to resilience include social support, empathy, emotional control, and freedom from societal expectations. Additionally, specific elements such as peer encouragement, mental health awareness, humor, and mindset play significant roles. Attachment to the deceased father can heighten an individual's vulnerability to grief.